EVALUATION OF THE QUEUE SYSTEM OF A DRIVING LICENSE APPLICATION AT KEPOLISIAN SUMBAWA BESAR - Hermanto, Koko; Ruskartina, Eki; Adiasa, Iksan; Hudaningsih, Nurul; P, Gipari Royen; Harizahayu, Harizahayu (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
A driving License (SIM) is a card that a motorized vehicle driver must own to prove the eligibility to drive a motorized vehicle. There are still many drivers who do not have a SIM. One of the reasons drivers don't apply for a driving license is because they object to follow every procedure in making a driver's license, which takes a long time and causes long queues every day. The application for a driver's license in a city or district is only in one place, namely at the City Police. As a result, many applicants apply for a driver's license in the queue system. This problem also occurs in the SIM-making service system at the Sumbawa Police Station. Therefore, this study aims to evaluate the queuing system for SIM-making services at the Sumbawa Besar Resort Police using the queuing theory method. There are two types of submissions in applying for a SIM, namely a new application and an application for an extension of a SIM, and the queuing system model used is Single Channel-Multi Phase. There are three phases in applying for a new SIM: the registration phase, photo phase, and test phase. Meanwhile, the application for a SIM extension has two steps: registration and photos. Based on the results of the analysis, the use of one service in each phase has not been optimal in overcoming the number of queues in the new SIM application process because there is still a steady-state (ρ) greater than one and the number of applicants is still queuing in the system, namely on Monday (phase test), Wednesday (test phase) and Friday (photo phase and test phase). Therefore, it is proposed to add one more service on that day and phase so that the stadium condition (ρ) is less than one and there is only one applicant in the queue (Lq).